2006
DOI: 10.2215/cjn.00500705
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Hypercalcemia with Cinacalcet after Kidney Transplantation

Abstract: Cinacalcet, a calcimimetic, was evaluated in persistent hyperparathyroidism after kidney transplantation (Tx). Ten kidney transplant recipients and one kidney-pancreas recipient with persistent post-Tx hypercalcemia (serum calcium [SCa] > 10.2 mg/dl), stable graft function, and intact parathyroid hormone (iPTH) >2 times normal received 30 mg/d cinacalcet between 2 mo and 5 yr after Tx. SCa, serum phosphorus (SP), and iPTH were measured before and after cinacalcet. Mean pre-cinacalcet SCa was 10.9 mg/dl (8.6 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 20 publications
2
58
1
4
Order By: Relevance
“…Control of serum calcium may be achieved by a parathyroidectomy, but this often occurs at the expense of transient or persistent hypoparathyroidism (41,42). Data from several small series indicate that treatment with cinacalcet, a calcimimetic, might be an attractive alternative for the treatment of hypercalcemia in renal transplant recipients (43)(44)(45)(46)(47)(48)(49). A randomized, double-blind, placebo-controlled study has been initiated to evaluate the efficacy and safety of using cinacalcet to correct hypercalcemia in incident renal transplant recipients with autonomous hyperparathyroidism (EudraCT 207-000573-29).…”
Section: Discussionmentioning
confidence: 99%
“…Control of serum calcium may be achieved by a parathyroidectomy, but this often occurs at the expense of transient or persistent hypoparathyroidism (41,42). Data from several small series indicate that treatment with cinacalcet, a calcimimetic, might be an attractive alternative for the treatment of hypercalcemia in renal transplant recipients (43)(44)(45)(46)(47)(48)(49). A randomized, double-blind, placebo-controlled study has been initiated to evaluate the efficacy and safety of using cinacalcet to correct hypercalcemia in incident renal transplant recipients with autonomous hyperparathyroidism (EudraCT 207-000573-29).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Serra et al (81) showed in a short study of 10 wk duration that cinacalcet was effective in correcting the hypercalcemia and reducing PTH values in patients who received a transplant and had persistent hyperparathyroidism. Finally, a recent retrospective study showed that cinacalcet was able to lower the serum calcium and increase serum phosphorus, with no significant changes in the PTH values (82). Nevertheless, Boulanger et al (83) showed a therapeutic failure of cinacalcet in a single case report.…”
Section: Role Of Calcimimeticsmentioning
confidence: 98%
“…As shown by Srinivas et al, calcimimetic agents can effectively suppress serum Ca in patients who have persistent secondary hyperparathyroidism and hypercalcemia after kidney transplant (8). Using low-dose cinacalcet, the investigators were able to effectively treat hypercalcemia while modestly suppressing PTH.…”
mentioning
confidence: 98%